Transcription Factor E2F1 Knockout Promotes Mice White Adipose Tissue Browning Through Autophagy Inhibition - Xiong, Mingchen; Hu, Weijie; Tan, Yufang; Yu, Honghao; Zhang, Qi; Zhao, Chongru; Yi, Yi; Wang, Yichen; Wu, Yiping; Wu, Min (Frontiers in Physiology, 2021)
Obesity is associated with energy metabolic disturbance and is caused by long-term excessive energy storage in white adipose tissue (WAT). The WAT browning potentially reduces excessive energy accumulation, contributing an attractive target to combat obesity. As a pivotal regulator of cell growth, the transcription factor E2F1 activity dysregulation leads to metabolic complications. The regulatory effect and underlying mechanism of E2F1 knockout on WAT browning, have not been fully elucidated. To address this issue, in this study, the in vivo adipose morphology, mitochondria quantities, uncoupling protein 1 (UCP-1), autophagy-related genes in WAT of wild-type (WT) and E2F1-/- mice were detected. Furthermore, we evaluated the UCP-1, and autophagy-related gene expression in WT and E2F1-/- adipocyte in vitro. The results demonstrated that E2F1 knockout could increase mitochondria and UCP-1 expression in WAT through autophagy suppression in mice, thus promoting WAT browning. Besides, adipocytes lacking E2F1 showed upregulated UCP-1 and downregulated autophagy-related genes expression in vitro. These results verified that E2F1 knockout exerted effects on inducing mice WAT browning through autophagy inhibition in vivo and in vitro. These findings regarding the molecular mechanism of E2F1-modulated autophagy in controlling WAT plasticity, provide a novel insight into the functional network with the potential therapeutic application against obesity.